Scleroderma-like Syndrome in the Setting of Pembrolizumab Therapy for Non-Small Cell Lung Cancer: Diagnosis and Dermatologic Management - Davide Fattore; Teresa Battista; Mario De Lucia; Maria Carmela Annunziata; Gabriella Fabbrocini (Karger Publishers, 2022)
Immune checkpoint inhibitors play an important role in the treatment of malignancies. ICIs consist of monoclonal antibodies directed against inhibitory immune receptors cytotoxic T-lymphocyte antigen 4 (CTLA-4), programmed cell death 1 (PD-1), or programmed cell death-ligand 1 (PD-L1). PD-1 is a receptor expressed by T lymphocytes and has the role of inhibiting their activation. Pembrolizumab is a humanized anti-PD-1 monoclonal antibody. It can improve the immune function of T-cells, which results in significant clinical benefit in the treatment of cancer. Despite its wide use, immunotherapy is associated with a spectrum of side effects known as immune-related adverse events. We present a case of an 82-year-old patient with widespread fibroatrophic skin areas that occurred during a treatment with pembrolizumab for non-small cell lung cancer. Clinical, serological, and histopathological examinations led to the diagnosis of generalized morphea. The patient discontinued pembrolizumab and switched to chemotherapy with pemetrexed and carboplatin. A good therapeutic response was obtained with phototherapy, corticosteroids, and topical calcineurin inhibitors. A focus on the therapeutic management of this skin toxicity in oncological patients is provided.